2011
DOI: 10.2478/v10096-011-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Long- to short-term denudation rates in the southern Apennines: geomorphological markers and chronological constraints

Abstract: Age constraints of geomorphological markers and consequent estimates of long-to short-term denudation rates from southern Italy are given here. Geomorphic analysis of the valley of the Tanagro River combined with apatite fission track data and radiometric dating provided useful information on the ages and evolution of some significant morphotectonic markers such as regional planated landscapes, erosional land surfaces and fluvial terraces. Reconstruction of paleotopography and estimation of the eroded volumes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 42 publications
(71 reference statements)
3
34
0
Order By: Relevance
“…As above reported, apatite fission-track data from rocks belonging to different tectonic units of the axial zone of the southern Apennines Mazzoli et al 2008) indicate a concordant final cooling age of ca 2.5-2.6 Ma (average value, Gioia et al 2011a;Schiattarella et al 2013), suggesting a widespread exhumation during the Late Pliocene. Since apatite passed the closure temperature isotherm at about 2.5 Ma, a considerable (~2 km) exhumation/denudation was needed to reach the surface.…”
Section: Morphotectonicssupporting
confidence: 51%
See 1 more Smart Citation
“…As above reported, apatite fission-track data from rocks belonging to different tectonic units of the axial zone of the southern Apennines Mazzoli et al 2008) indicate a concordant final cooling age of ca 2.5-2.6 Ma (average value, Gioia et al 2011a;Schiattarella et al 2013), suggesting a widespread exhumation during the Late Pliocene. Since apatite passed the closure temperature isotherm at about 2.5 Ma, a considerable (~2 km) exhumation/denudation was needed to reach the surface.…”
Section: Morphotectonicssupporting
confidence: 51%
“…Relative and absolute dating of the summit palaeosurface indicated that it developed in the Late Pliocene, but the planation process was still active during the Early Pleistocene (Gioia et al 2011a;Schiattarella et al 2013). The morphological de-activation of a land surface is achieved when it undergoes to a significant tectonic hanging and acquires the condition of relict landform.…”
Section: Morphotectonicsmentioning
confidence: 99%
“…This complex geological framework accounts for the presence of a variety of lithologies, different in age, composition and lithotechnical properties. Taking into consideration the geological map of Bonardi et al (1988) The geomorphological setting of the study area is strongly controlled by geological and structural conditions (Gioia, Martino, & Schiattarella, 2011). In fact, the distribution of the lithological units, with respective geotechnical properties, influence the slope dynamics and the nature of the geomorphic processes.…”
Section: Geographical Geological and Geomorphological Frameworkmentioning
confidence: 99%
“…4), representing a remnant of a regional planation surface, late Pliocene -early Pleistocene in age (Schiattarella et al, 2003Boenzi et al, 2004;Gioia et al, 2011).…”
Section: Fig 2 Location Of the Study Area In The Tectonic Scheme Ofmentioning
confidence: 99%
“…8b) and the reworking of the pre-existing upper Pliocene -lower Pleistocene summit land surface (palaeosurface or "Paleosuperficie" Auctt., S1 after Schiattarella et al, 2003, cf. age constrain in Gioia et al, 2011); -third stage: both the regional uplift at about 1.2 Ma ("Emilian" tectonic stage, cf. Ruggieri et al, 1984), responsible for the displacement of the palaeosurface, and the instauration of a humid climate regime, favouring the fluvial erosion, promoted the vertical incision by streams of the morpho-structural low previously created; successively, the lateral planation of the valley in a steady-state fluvial condition, produced an erosional glacis in the shaly Lagonegro-type units of the downthrown block (Fig.…”
Section: Morpho-evolutionary Sequencementioning
confidence: 99%